« La tête vers le lever du soleil… » - Vaté, Virginie (Études mongoles et sibériennes, centrasiatiques et tibétaines, 2009)
Through a comparison of data collected among Chukchee reindeer herders in two different regions of Chukotka (Amguema and Kanchalan), this article investigates the issue of spatial orientation in the domestic sphere in everyday life and in ritual, with two main goals: 1) to emphasize that the translation of Chukchee terminology of orientation with terms of absolute directions (north, south, etc.) is not reliable; and 2) to show that orientation is not only a way of organizing and appropriating space, but also represents a means of marking and defining different domains of life. En comparant les matériaux recueillis chez les éleveurs de rennes tchouktches de deux régions de Tchoukotka (Amgouema et Kantchalane), cet article explore la question de l’orientation au sein de la sphère domestique en contexte quotidien et rituel, avec deux objectifs principaux : 1) souligner que la traduction de la terminologie d’orientation tchouktche en termes de direction absolue (nord, sud, etc.) n’est pas fiable; 2) montrer que l’orientation est non seulement une manière d’organiser et de s’approprier l’espace, mais aussi constitue un moyen de marquer et de définir les différents registres de la vie.